Integrating Nature, Culture, and Development: The Challenge of LXG Capital in a Forest Restoration Program - Roca-Alcázar, Fernando (2023)
The effects of development proposals on road infrastructure can adversely affect the ecosystem. The case of the interoceanic road in southern Peru is an example. This article discusses the first results of a forest restoration project in a degraded area, Iñapari, Peruvian Amazon, Madre de Dios region, bordering Brazil. The concept of Integral Ecology has been the reference for its development. In addition, forest restoration is part of what is called Ecological Restoration.